Tap Learning Model as an Effort to Build the Perfect Character of the Congregation of the Voice of Truth Gospel Church in Medan - Rinto Francius Sirait (International Perspectives in Christian Education and Philosophy, 2025)
The aim of this study is to develop and produce findings on an effective teaching model to build the perfect character of the congregation of the Suara Sejati Gospel Church in Medan. The research method used in this study is a qualitative method with a phenomenological approach. The data sources used in this study are a semi-structured interview guide and field notes. The data analysis technique used in this study involves several steps, namely bracketing, horizontalization, phenomenological reduction, and synthesis of essential meaning. The results of the study indicate that: The congregation and servants of God GSKI in Medan City identified several key attributes in achieving perfect character which include high moral quality, holiness, commitment to following God's will, and growth in faith through deepening the Word and fellowship; The congregation of GSKI in Medan City faces several major challenges in building perfect character according to the teachings of Matthew 5:48, such as limitations in understanding the teachings of the Bible and incomplete doctrines, worldly influences and attachment to worldly pleasures, and the lack of consistent role models from church leaders; An effective teaching model for building perfect character based on Matthew 5:48 in the context of the GSKI congregation in Medan City consists of a structured teaching approach, practical and contextual application, and role models and leadership; An effective teaching model for building perfect character based on Matthew 5:48 is a model that is transformative, andragogical, and empowering. This study produces the TAP Model (Transformation - Andragogy - Empowerment) which includes the stages of introduction, reflection, practice, as well as evaluation and mentoring. This model encourages active congregational involvement, connects the Word with real life, and forms character through a contextual and spiritual learning process.